Issues in digital cataloguing - Mishra, Anmol Ratan (Shree, 2004)
Contents of material: 1/ Cataloguing in the digital age. 2/ Cataloguing digital resources. 3/ Archiving and preserving digital information. 4/ Digital preservation strategy. 5/ Archival information system. 6/ Issues in digital archiving.